Technology Acceptance Models of E-Commerce Adoption in Small and Medium-Sized Enterprises: A Systematic Review - Nur Hadian; Nur Hayati; Mujibul Hakim (G-Tech: Jurnal Teknologi Terapan, 2024)
Various review studies on the Technology Acceptance Model (TAM) have provided recent insights into research trends, especially regarding e-commerce adoption. However, this study highlights the knowledge gap in TAM investigations related to e-commerce adoption in the context of small and medium enterprises (SME). Through a systematic review of 28 research articles from 2018 to 2023, the main findings show that TAM research tends to focus on developing models with external variables, especially factors from other theories or models. The main issue that is often discussed is the acceptance of e-commerce at the micro-industry scale, with surveys as the dominant research method. This study provides valuable insights and becomes an important reference for academics, professionals, and business people interested in e-commerce adoption in SMEs, highlighting key trends and issues that need further research.